The sialyltransferase ST6GAL1 protects against radiation-induced gastrointestinal damage. (2nd January 2020) - Punch, Patrick R; Irons, Eric E; Manhardt, Charles T; Marathe, Himangi; Lau, Joseph T Y
Abstract: High-dose irradiation poses extreme risk of mortality from acute damage to the hematopoietic compartment and gastrointestinal tract. While bone marrow transplantation can reestablish the hematopoietic compartment, a more imminent risk of death is posed by gastrointestinal acute radiation syndrome (GI-ARS), for which there are no FDA-approved medical countermeasures. Although the mechanisms dictating the severity of GI-ARS remain incompletely understood, sialylation by ST6GAL1 has been shown to protect against radiation-induced apoptosis in vitro. Here, we used a C57BL/6 St6gal1 -KO mouse model to investigate the contribution of ST6GAL1 to susceptibility to total body irradiation in vivo. Twelve gray total body ionizing γ-irradiation (TBI) followed by bone marrow transplant is not lethal to wild-type mice, but St6gal1 -KO counterparts succumbed within 7 d. Both St6gal1 -KO and wild-type animals exhibited damage to the GI epithelium, diarrhea and weight loss, but these symptoms became progressively more severe in the St6gal1 -KO animals while wild-type counterparts showed signs of recovery by 120 h after TBI. Increased apoptosis in the GI tracts of St6gal1 -KO mice and the absence of regenerative crypts were also observed. Together, these observations highlight an important role for ST6GAL1 in protection and recovery from GI-ARS in vivo.